Tra Sagres e Lisbona. Musei di storia e identitá nazionale nell’Estado Novo portoghese - Gori, Annarita (2017)
The Portuguese national identity is closely linked to the deeds of the Age of Discovery. During the long period of the Estado Novo (1933-1974) the regime extensively resorted to the myth of descobridores to legitimize itself, build consensus and self-represent. One of the most interesting examples in this regard is the monument and the museum dedicated to Henry the Navigator on the Sagres promontory. The regime launched three contests – in 1933, 1936 and 1954 – but all were resolved in stalemate. This article aims to analyze the different solutions presented in the three contests, taking into consideration the museum as a socio-political institution that, through collections and exhibitions, conveyed myths and value and tried to build a shared national identity. Furthermore the long-term approach allowed for the investigation of difficulties in representing the National past in relation to political and social vicissitudes, both nationally and internationally, and the consequent change in the museum setting over a period of almost thirty years.